Fine Art as an Anthropological Source - Shpak, Larisa I.; Perevozchikov, Il’ia V. (Actual Problems of Theory and History of Art, 2021)
Already in the early stages of the development of anthropology as an independent branch of knowledge, researchers focused on fine art as a source of anthropological information. Before the era of photography, information about a person’s appearance could be obtained either from his description by contemporaries, or from his lifetime portraiture. In anthropology, the main method of obtaining information about the biological characteristics of the ancient population is the study of bone remains. Both approaches were combined in the method of anthropological face reconstruction (M. M. Gerasimov), but some important features (for example, pigmentation, hair shape, etc) remain outside the description system. The authors have applied not an individual-typological, but a population approach to the study of human images. A group of images has been analyzed as a sample of individuals from the same territory and chronological period with the calculations of ordinary statistics and the construction of composite portraits (F. Galton’s method). This approach enables us to visualize the images of the ancient and modern population of Europe by portraiture. Determining descriptive morphological features, a standard set of scales accepted in anthropology was used. Composite images were constructed and analyzed for modern groups, such as Russian portrait painting of the 17th–19th centuries and European portraiture of the 16th–17th centuries. Among ancient groups, Fayum burial portraits and Etruscan-Roman votive terracotta heads have been examined. The anthropological study of fine art is promising both in the research of the ethnogenesis of the ancient population groups of Europe, and in the study of the early stages of portraiture.